Menggali Hikmah: Urgensi Memahami I’jazul Qur’an dalam Suroh Lukman Ayat 16 - Fadhil, Muhammad Bayu; Muhaddar, Rifki; Alrasyid, Harun (TSAQOFAH, 2024)
The delivery of the moral message in the case study of Suroh Lukman verse 16 discusses the importance of understanding miracles and wisdom in Islam. In this study, researchers focus on the importance of understanding miracles and wisdom in Islam. Miracles in the Al-Qur'an can be interpreted as philosophical activity, social reinforcement, and control of power. The method of research used is a method is qualitative which uses an interpretive approach to the Al-Qur'an to explore the wisdom and miracles contained therein. in this research using textual analysis of suroh lukman verse 16, this research discusses the importance of understanding miracles and wisdom in Islam and discusses how the verses contained in suroh lukman can be integrated into moral and character education in the Islamic education environment, in this research also allows researchers to explore it in terms of historical, linguistic and theological context. The understanding of this verse is s follows: first,certainty and knowledge and power of allah. second, advice to children. Third, moral and ethical awareness. Fourth, motivation to do good.